Integrating photovoltaic distributed generation and reactive power compensation for sustainable power distribution networks - Sree Ram, Kirthy Manimaran; Mohd Saad, Norhafidzah; Azmi, Siti Hajar; shankara, Nandhana; Abas, Mohammad Fadhil; Pebrianti, Dwi (IEEE, 2025)
This study addressed voltage regulation, power losses, and efficiency challenges in medium- and low-voltage distribution networks by implementing a four-stage enhancement strategy: i) base case evaluation, (ii) network reconfiguration by adding transmission lines, (iii) integration of photovoltaic distributed generation (PVDG), and (iv) installation of capacitor banks for reactive power compensation. The system was modeled and analyzed in DIgSILENT PowerFactory. Results showed a 29.4% reduction in active power losses from 1.7 MW to 1.2 MW and a 39.6% drop in reactive power losses (5.3 MVar to 3.2 MVar). The active and reactive power imported from the 132 kV grid decreased by 35.2% and 50.7% respectively, while voltage magnitudes at substations stabilized at 1.0 p.u. The findings demonstrated that coordinated deployment of PVDG and capacitor banks, combined with network reconfiguration, significantly improved voltage stability, reduced losses, and enhanced system reliability, thus supporting the shift toward sustainable distribution networks.